Exploiting White-Light Observations to Improve Estimates of Magnetic Connectivity - Poirier, Nicolas; Rouillard, Alexis P.; Kouloumvakos, Athanasios; Przybylak, Alexis; Fargette, Naïs; Pobeda, Raphaël; Réville, Victor; Pinto, Rui F.; Indurain, Mikel; Alexandre, Matthieu (Frontiers in Astronomy and Space Sciences, 2021)
The Solar Orbiter (SolO) and Parker Solar Probe (PSP) missions have opened up new challenges for the heliospheric scientific community. Their proximity to the Sun and their high quality measurements allow us to investigate, for the first time, potential sources for the solar wind plasma measured in situ. More accurate estimates of magnetic connectivities from spacecraft to the Sun are required to support science and operations for these missions. We present a methodology to systematically compare coronal and heliospheric models against white-light (WL) observations. White-light images from the SOlar and Heliospheric Observatory (SoHO) are processed to unveil the faint structures of the K-corona. Images are then concatenated over time and are projected into a Carrington synoptic map. Features of interest such as the Streamer Belt (SB) are reduced to simplified geometric objects. Finally, a metric is defined to rank models according to their performance against WL observations. The method has been exploited to reproduce magnetic sectors from WL observations. We tested our results against one year of in situ magnetic polarity measurements taken at near 1 AU from the Advanced Composition Explorer (ACE) and the Solar TErrestrial RElations Observatory (STEREO-A). We obtained a good correlation that emphasizes the relevance of using WL observations to infer the shape of the sector structure. We show that WL observations provide additional constraints to better select model parameters such as the input photospheric magnetic map. We highlight the capability of this technique to systematically optimize coronal and heliospheric models using continuous and near-real-time WL observations. Several relevant practical applications are discussed, which should allow us to improve connectivity estimates.